Sustained Upwelling of Subsurface Iron Supplies Seasonally Persistent Phytoplankton Blooms Around the Southern Kerguelen Plateau, Southern Ocean. Issue 8 (29th August 2018) - Schallenberg, Christina; Bestley, Sophie; Klocker, Andreas; Trull, Thomas W.; Davies, Diana M.; Gault‐Ringold, Melanie; Eriksen, Ruth; Roden, Nicholas P.; Sander, Sylvia G.; Sumner, Michael; Townsend, Ashley T.; van der Merwe, Pier; et al.
Abstract: Although the supply of iron generally limits phytoplankton productivity in the Southern Ocean, substantial seasonal blooms are observed over and downstream of the Kerguelen plateau in the Indian sector of the Southern Ocean. Surprisingly, of the oceanic blooms, those associated with the deeper southern plateau last much longer (~3 months) than the northern bloom (~1‐month downstream of northern plateau). In this study, iron supply mechanisms around the southern plateau were investigated, obtaining profiles of dissolved iron (<0.2 μm, dFe) to 2, 000‐m deep at 25 stations during austral summer 2016. The dFe concentrations in surface waters (≤100‐m depth) ranged from below the detection limit (DL, median of 0.026 nmol/kg) to 0.34 nmol/kg near the Antarctic shelf, with almost half the data points below detection. These low and—with few exceptions—largely spatially invariant concentrations, presumably driven by seasonal drawdown of this essential micronutrient by phytoplankton, could not explain observed patterns in chlorophyll a . In contrast, dFe concentrations (0.05–1.27 nmol/kg) in subsurface waters (100–800 m) showed strong spatial variations that can explain bloom patterns around the southern Kerguelen plateau when considered in the context of frontal locations and associated frontal processes, including upwelling, that may increase the upward supply of dFe in the region. This sustained vertical dFe supply distinguishes the southern blooms from the bloom downstream of the northern Kerguelen plateau and explains their persistence through the season. Plain Language Summary: Over much of the Southern Ocean, phytoplankton productivity is hampered by a lack of dissolved iron, an essential micronutrient for phytoplankton. However, there are areas where phytoplankton thrive, and these are often associated with topographic features. For example, a large phytoplankton bloom develops each year downstream of the northern Kerguelen plateau. This bloom peaks around December and subsequently declines. It receives its iron supply mainly from the sediments on the shallow plateau, carried downstream in surface waters with the currents. There are also blooms near the much deeper (>1, 000 m) southern Kerguelen plateau, but the supply of iron to these blooms was poorly understood until now. These blooms persist through the growing season and thus outlast the bloom downstream of the northern Kerguelen plateau. Our study results indicate that the southern blooms receive their iron from the subsurface, and that the source of the iron likely includes Antarctic shelf sediments and remineralization of sinking material. Localized upwelling associated with the wind and current patterns in the region brings this subsurface iron to the surface, where it fuels phytoplankton growth. The key to the longevity of the blooms thus appears to be the combination of a subsurface iron source and persistent upwelling. Key Points: Subsurface dissolved iron concentrations around the southern Kerguelen plateau were more variable than surface concentrations Sustained upwelling of subsurface iron is the most likely mechanism supplying iron to the persistent phytoplankton blooms in the region Horizontal advection of subsurface iron and upwelling associated with the Antarctic Divergence combine to create a biological hot spot